Head loss in screen and disc filters using a data acquisition system - Testezlaf, Roberto; Ramos, Jean Paulo da Silva (Pesquisa Agropecuaria Brasileira, 1995)
The objective of this study was to evaluate the head loss through disc and screen filters installed in trickle irrigation control head using data acquisition and analysis system. Basically, the acquisition system is composed by pressure and flow transducers connected to signal conditioner, A/D converter and controlled by a PC microcomputer. The results showed that the mathematical behavior of the head loss for both type of filters could be explained significantly at level of 1%, by the power function Hf=a.Qb. Despite the mesh and flow used, the disc filters had higher values of head loss when compared to screen filters. For the disc filters, the mesh 155 had head loss values higher than the mesh 120, and for the screen filters the difference of the head loss values between the two meshes was not significant. The developed acquisition system showed a good performance during the tests, having no failure or misfunctioning which could lead to misunderstanding the acquisition and the analysis of data.